Synod diecezji kujawskiej i pomorskiej z 1586 roku - Borucki, Janusz (Prawo Kanoniczne, 2003)
Activities of Bishop Hieronim Rozrażewski has occurred in the time of initiation and realization of the Tridentine Council resolutions. In the time of his administration in the diocese of Włocławek (named at that time Kujawy and Pomeranian) he had carried on seven synods. Three of them (in 1586,1589 and 1590) were diocesan synods. The rest (in 1585,1589,1590 and 1598) included pomeranian archdeacon’s district only. The most important of them is diocesa synod carried of 1586. The content of the synodal statutes of Bishop Rozrażewski was constituted of numerous legal regulations and pastoral instructions. Its problems contained wide range of matters pertaining various fields of ecclesiastical life. More rigorous analysis of the content of the statutes entitles to differentiation of several thematic groups: defence of the catholic faith, administration and reception of the sacra-ments, other forms of God’s worship, times and holy places, benefices and the duties of the incumbents, the diocesan offices, the discipline of the clergy, monastic life, ecclesiastical seminary, church’s property. Bishop Hieronim Rozrażewski’s synod carried of 1586 constituted very important stage in the process of realization of the tridentine reforms in the Kujawy and Pomeranian diocese initiated by Bishop Stanisław Karnkowski.